2018
DOI: 10.1590/1980-5373-mr-2017-0745
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cryogenic Treatment on the Tribological Behaviour of AISI H21 Tool Steel

Abstract: The aim of the present work was to find out the optimum cryosoaking duration of deep cryogenic treatment to reduce the wear rate. The AISI H21 hot work tool steel specimens were hardened at 1195 ºC, cryotreated at-185 ºC for 6 to 30 h, double tempered at 540 ºC and soft tempered at 100 ºC. The hardness, impact toughness, wear rate and microstructural characteristics of the cryotreated specimens were studied. Wear test parameters were optimized by using Taguchi technique. Analysis of variance and signal to nois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Then the relative proximity index of each alternative to the ideal solution called as closeness coefficient is computed by the ratio of the positive solution to the sum of ideal solutions (table 7(b)). The closeness coefficients are analyzed by standard Analysis of means (table 8) and Analysis of variance (table 9) based on the methodology suggested by Taguchi [16][17][18][19][20][21][22].…”
Section: Results and Analysismentioning
confidence: 99%
“…Then the relative proximity index of each alternative to the ideal solution called as closeness coefficient is computed by the ratio of the positive solution to the sum of ideal solutions (table 7(b)). The closeness coefficients are analyzed by standard Analysis of means (table 8) and Analysis of variance (table 9) based on the methodology suggested by Taguchi [16][17][18][19][20][21][22].…”
Section: Results and Analysismentioning
confidence: 99%
“…The CVN impact toughness increased by more than 50% for cryogenically treated (at −196 • C for 6 h, sequence A) hot stamping CR7V steel, besides a remarkable hardness increase of 80 HV [271]. The result of cryogenically treated AISI H21 steel (at −185 • C for 6-30 h, following sequence F) was the opposite [269]. Cryogenic treatment led to a general toughness decrease, with the lowest value recorded after 24-h of treatment.…”
Section: Hot Work Tool Steelsmentioning
confidence: 95%
“…Despite considerable inconsistencies in the test conditions (counterpart nature, load, sliding speed, and distance), some general outcomes can be derived. For AISI H11, H13, and H21 steels, a 16-24 h treatment at −184 • C (or −185 • C) was recommended to achieve the lowest wear rate against steel counterparts [19,49,51,122,199,200,[259][260][261][262]269]. However, when hard alumina counterparts were used for wear performance examination, after CT at −180 • C for 32 h, there was only a 12% wear performance improvement in H13 steel [267].…”
Section: Hot Work Tool Steelsmentioning
confidence: 99%
“…To overcome the machining difficulties, Korade et al [11] proposed to enhance the properties of cutting tool materials with high resistance to wear and thermal resistance. Mukkoti et al [12] reported that the interaction effect between the cutting parameters would greatly influence the tool materials.…”
Section: Introductionmentioning
confidence: 99%